Implications of metabolic health status and obesity on the risk of kidney cancer: A nationwide population-based cohort study - Cho, Yun Kyung; Kim, Hwi Seung; Park, Joong-Yeol; Lee, Woo Je; Kim, Ye-Jee; Jung, Chang Hee (Frontiers in Endocrinology, 2022)
Purpose: This study evaluated the association between metabolic health status and incident kidney cancer among obese participants. Materials and methods: A total of 514,866 individuals were included from the Korean National Health Insurance Service-National Health Screening Cohort. Changes in metabolic health status and obesity from the baseline examination in 2009–2010 to the next biannual examination in 2011–2012 were determined. Based on the status change, obese participants were divided into four groups: stable metabolically healthy obesity, metabolically healthy obesity to metabolically unhealthy obesity, metabolically unhealthy obesity to metabolically healthy obesity, and stable metabolically unhealthy obesity. Results: The stable metabolically healthy obesity phenotype did not confer an increased risk of incident kidney cancer, compared to the stable metabolically healthy non-obese group. In contrast, the metabolically healthy obesity to metabolically unhealthy obesity group had a significantly higher risk of incident kidney cancer than the stable metabolically healthy non-obese group. Among patients with metabolically unhealthy obesity at baseline, those who transitioned to the metabolically healthy obese group had no increased risk of kidney cancer, whereas those who remained in metabolically unhealthy obesity status had a higher risk of incident kidney cancer than the stable metabolically healthy non-obese group. The transition or maintenance of metabolic health was a decisive factor for kidney cancer in obese patients. Conclusions: Maintaining or restoring metabolic health should be stressed upon in obese patients to reduce the risk of kidney cancer.